Integrated crop and livestock planning under minor irrigation command area - PARAMJITA, D.; PANIGRAHI, B.; PAUL, J. C. (Journal of Soil and Water Conservation, 2020)
In this paper, the linear programming model is used and the problem is solved through LINDO software for integrated crop and livestock planning in Gunduraposi minor irrigation project located at Dhenkanal district, Odisha. The objective of the study was to maximise profit and crop production and to minimise investment in production. While considering maximisation of profit (net return maximization) the area of rice crop was 58.7% of the command area whereas in case of maximising production the same rice crop came around 62% of command area. In case of minimisation of investment the rice crop was around 56% of command area. Profit was reduced by 1.92% and 7.22% in production maximisation and invest minimisation model compared to net return maximization model, respectively. The decision maker can accordingly come to a decision about the allocation of crop according to his prospective.